ANALISIS DINDING PENAHAN TANAH PADA SUNGAI BRANG BIJI - Riska Handayana; Dedy Dharmawansyah; Eti Kurniati; Adi Mawardin (Hexagon Jurnal Teknik dan Sains, 2020)
Brang Biji River is one of the rivers prone to flooding. Flooding occurs can result in a collapse in the construction of the retaining walls of the soil causing substantial harm to the surrounding community. It takes an alternative in maintaining the stability of slopes to reduce the avalanche in the Brang Biji River. Alternative wall retaining walls namely pairs of stone times and Sheet Pile, while comparative analysis to determine the type of effective construction used in the Brang Biji river using manual calculation method and software Plaxis 8.6. Data collection through field surveys, to get soil type data, geometrics slopes, and soil layer. To get the stability of slope in existing condition, in case of a cladding with SF ? 1 criteria using method of reverse analysis or approach based on trial and error literature. Results obtained from the reverse analysis are used for the analysis of the compoon on the slope of the Brang Biji River, either by manual calculation or Software Plaxis 8.6 In determining the value of SF. After analysis of the stability of the slope, obtained the result that by using a stone time retaining wall with a height of 5.5 m, the bottom width of 3.85 m, the upper width of 0.6 m with a depth of 1.5 m from the ground surface and the height of the river water face around 7.8 m , both against the bolsters with SF = 3.4, against sliding with SF = 2.17 and the power of land with SF = 3 manually while using the Plaxis Software with the addition of the working floor with a thickness of 10 cm and piling with a diameter of 40 cm with a distance of 25 cm obtained SF = 1.26. Whereas by using Sheet Pile use manual calculation obtained depth (D) Sheet Pile about 2.43 m with a large stability backup (SF) = 1.5 D and the length of Sheet Pile as a whole about 8.43 m from ground level, while using Plaxis obtained value SF = 1,167.